INTERNALISASI PROFESI BIMBINGAN DAN KONSELING PADA MAHASISWA BIMBINGAN DAN KONSELING FIP UNY - Muhammad Nur Wangid (Jurnal Penelitian Ilmu Pendidikan, 2010)
The objective of this research was to describe the internalization of guidance and counseling profession, and to compare the degree of internalization based on semester of guidance and counseling profession of guidance and counseling students. The population was guidance and counseling students of the Faculty of Educational Scienties on the odd semester 2008/2009 totally 588. The proporsional stratified random sampling technique was used to find the sample 202 students. The main method was questionare that supported by observation and interview. Descriptive analisys and One Way ANOVA employed to analysis teh data. The result show that the degree of internalization of guidance and counseling profession lay on medium category agree with development of the degree of semester. The guidance and counseling students difference in the degree of internalization in each semester. The students of regular and non-regular difference in internalize the value of guidance and counseling profession, but they are not difference especially in gender. Key Words: Internalization; Guidance and Counseling Profession; Guidance and Counseling Students